Rac and Arp2/3-Nucleated Actin Networks Antagonize Rho During Mitotic and Meiotic Cleavages - Pal, Debadrita; Ellis, Andrea; Sepúlveda-Ramírez, Silvia P.; Salgado, Torey; Terrazas, Isabella; Reyes, Gabriela; De La Rosa, Richard; Henson, John H.; Shuster, Charles B. (Frontiers in Cell and Developmental Biology, 2020)
In motile cells, the activities of the different Rho family GTPases are spatially segregated within the cell, and during cytokinesis there is evidence that this may also be the case. But while Rho’s role as the central organizer for contractile ring assembly is well established, the role of Rac and the branched actin networks it promotes is less well understood. To characterize the contributions of these proteins during cytokinesis, we manipulated Rac and Arp2/3 activity during mitosis and meiosis in sea urchin embryos and sea star oocytes. While neither Rac nor Arp2/3 were essential for early embryonic divisions, loss of either Rac or Arp2/3 activity resulted in polar body defects. Expression of activated Rac resulted in cytokinesis failure as early as the first division, and in oocytes, activated Rac suppressed both the Rho wave that traverses the oocyte prior to polar body extrusion as well as polar body formation itself. However, the inhibitory effect of Rac on cytokinesis, polar body formation and the Rho wave could be suppressed by effector-binding mutations or direct inhibition of Arp2/3. Together, these results suggest that Rac- and Arp2/3 mediated actin networks may directly antagonize RhoA signaling, thus providing a potential mechanism to explain why Arp2/3-nucleated branched actin networks must be suppressed at the cell equator for successful cytokinesis.